Mesomorphic, electro-optic and structural properties of binary liquid crystalline mixtures with ferroelectric and antiferroelectric liquid crystalline behaviour. (3rd October 2018) - Fitas, Jakub; Marzec, Monika; Szymkowiak, Marta; Jaworska-Gołąb, Teresa; Deptuch, Aleksandra; Tykarska, Marzena; Kurp, Katarzyna; Żurowska, Magdalena; Bubnov, Alexej
ABSTRACT: Two new binary liquid crystalline mixtures composed from the chiral liquid crystalline materials with partially fluorinated non-chiral chain and without lateral substitution at the molecular core have been designed and investigated by polarisation optical microscopy, differential scanning calorimetry, broad-band dielectric spectroscopy, and X-ray techniques. Both mixtures possess the paraelectric orthogonal smectic A*, the tilted ferroelectric smectic C* and the antiferroelectric smectic CA * phases over a reasonably broad temperature range. The gained results reveal a considerable improvement of (i) the broadness of the mesophases temperature range of the ferroelectric and antiferroelectric phases (up to 130 K breadth) and (ii) electro-optical properties, namely the spontaneous polarisation (up to 200 nC/cm 2 ) and tilt angle (higher than 40 o ), with respect to that of the original pure compounds.